Hadron spectroscopy (theory): Diquarks, tetraquarks, pentaquarks and no quarks - Close, F (2005)
States beyond those expected in the simple constituent quark model are now emerging. I focus on the scalar glueball and its mixing with states in the qq nonet, and also on correlations in Strong QCD that may form diquarks and seed qqqq states. Some models of the pentaquark candidate theta(1540) are critically discussed.